Search Engine Get Application Programming Interface - Muri, M. Fuadi Aziz; Utomo, Hendrik Setyo; Sayyidati, Rabini (Jurnal Sains dan Informatika, 2019)
Application Programming Interface (API) is a function concept that can be called by other programs. The API works as a link that unites various applications of various types of platforms, commonly known as API public names. The public API has been widely spread, while its users, programmers who want to search for public APIs, must browse through various methods such as general search engines, repository documentation or directly in web articles. The user does not yet have a system specifically for collecting public-public APIs, so that users have difficulty in performing API public link searches. The solution to these problems can be solved by building a web framework with a search engine interface that provides specific public-public searches for the API, so that users can search the API public more easily. Web Service is an API that is made to support the interaction between two or more different applications through a network. Representational State Transfer (ReST) is one of the rules.